Banda Aceh الأخطاء الشائعة عند المتعلم في قراءة النصوص العربية بمعهد دار العلوم العصري - Mega, T. Fadlon; Suhaimi, Suhaimi; Ridha, Muhammad (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2022)
This research aims to identify the common errors in reading Arabic texts among students and to identify their causes. As for the research method, the researcher used a descriptive analytical method. Observation, interview, and documentation were used to collect data. After the researcher carried out the scientific research, I found that the common mistakes of the learner in reading Arabic texts are divided into two types, namely, grammatical errors and morphological errors. Grammatical errors were the most frequent errors in reading Arabic texts, with a total of 117, with a percentage of 92.12%, and morphological errors, totaling 10, with a percentage of 7,87%. The factors that cause common mistakes in the learner’s reading of Arabic texts consist of several factors, namely lack of knowledge of rules, neglect of rules, unwillingness in the Arabic language and lack of reading Arabic texts.